Proteomics reveals pathways linked to septoria canker resistance and susceptibility in Populus trichocarpa - Lenz, Ryan R.; Shrestha, Him K.; Carrell, Alyssa A.; Labbé, Jessy; Hettich, Robert L.; Abraham, Paul E.; LeBoldus, Jared M. (Frontiers in Analytical Science, 2022)
A major threat to forest ecosystems and plantation forestry is the introduction of a non-native pathogen. Among non-domesticated populations with relatively high levels of genetic diversity, a measurable range of susceptibility to resistance can be expected. Identifying genetic determinants of resistant and susceptible individuals can inform the development of new strategies to engineer disease resistance. Here we describe pathogen-induced changes in the proteome of Populus trichocarpa stem tissue in response to Sphaerulia musiva (Septoria canker). This hemibiotrophic fungal pathogen causes stem canker disease in susceptible poplar genotypes. Proteomics analyses were performed on stem tissue harvested across 0-, 12-, 24- and 48-hours post-inoculation with Septoria from three genotypes including one resistant (BESC-22) and two susceptible (BESC-801; Nisqually-1 (NQ-1)). In total, 11,897 Populus proteins at FDR < 0.01 were identified across all time points and genotypes. Analysis of protein abundances between genotypes revealed that the resistant poplar genotype (BESC-22) mounts a rapid and sustained defense response involving pattern recognition receptors, calcium signaling proteins, SAR inducers, transcriptional regulators, resistance proteins, and proteins involved with the hypersensitive response. One susceptible genotype (BESC-801) had a downregulated and delayed defense response whereas the second susceptible genotype (NQ-1) lacked a distinct pattern. Overall, the proteome-wide and protein-specific trends suggest that responses to the Septoria canker infection are genotype-specific for the naïve host, Populus trichocarpa.